Utilization of Infak in Literature Activities at Wadas Kelir Creative House - Hadi, Rahmini; Luthfi Hamidi, A.; Dwi Larasfeni, Fitria; Hesti Pratiwi, Pramudita (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Everyone has property basically he has the right to be given to others but not all of them are given. The concept of infaq is a form of worship that has two dimensions, namely, a vertical dimension and a horizontal dimension. One of the communities that uses the infaq system is the Wadas Kelir Creative House. Wadas Kelir Creative House manages literacy programs using infaq funds which are managed independently. Various literacy programs were launched with infaq funds, but there are many beneficial impacts in the field of education in the form of human resources who are willing to study seriously. Research conducted by researchers regarding the use of infaq in literacy activities at the Wadas Kelir Creative House in Karangklesem, South Purwokerto. This study aims to describe the use of Infaq in literacy activities. This study uses a qualitative descriptive field research method. The location under study was at Wadas Kelir Creative House in Karangklesem, South Purwokerto, with volunteers and founders as research subjects. The results showed that the use of infaq in literacy activities at the Wadas Kelir Creative House were (1) the benefits of infaq in activities, (2) the benefits of infaq in facilities, (3) the benefits of infaq in human resources, (4) the benefits of infaq in brotherhood. These four results of research become life in utilizing literacy-based education at Wadas Kelir Creative House.